THU0651 AN INDIVIDUALIZED DECISION-AID FOR DIVERSE WOMEN WITH LUPUS NEPHRITIS (IDEA-WON): A RANDOMIZED CONTROLLED TRIAL . (June 2019) - singh, jasvinder; Fraenkel, Liana; Green, Candace; Alarcon, Graciela S; Barton, Jennifer; Saag, Kenneth; Hanrahan, Leslie; Raymond, Sandra; Kimberly, Robert; Leong, Amye; Reyes, Elyse; Street, Richard; et al.
Abstract : Background: Medication decision-making is challenging in lupus. No validated, effective decision-aids are available to assist patients with medication decision-making. Objectives: Our objective was to assess the effectiveness of an individualized, culturally-tailored, computerized decision-aid for immunosuppressive medications for lupus nephritis. Methods: In a multicenter, randomized controlled trial, diverse adult women with lupus nephritis, largely racial/ethnic minorities with low socio-economic status, were randomized to decision-aid vs. American College of Rheumatology lupus pamphlet (1:1 ratio). Co-primary outcomes were change in decisional conflict and informed choice regarding immunosuppressive medications. Results: Of 301 randomized women, 47% were African-American, 26% were Hispanic, and 15% White. Mean age (standard deviation [SD]) was 37 (12) years, 57% had annual income of <40, 000, and 36% had a high-school education or less. Compared to the pamphlet (n=147), participants randomized to the decision-aid (n=151) had: (1) a clinically meaningful and statistically significant larger decrease in decisional conflict, 21.8 (standard error [SE], 2.5) vs. 12.7 (SE, 2.0; p=0.005); and (2) a clinically meaningful difference in informed choice, statistically non-significant in the main analysis, 41% vs. 31% (p=0.08), but significant in sensitivity analysis (net values for immunosuppressives positive [in favor] vs. negative [against]), 50% vs 35% (p = 0.006). Respectively, unresolved decisional conflict post-intervention was significantly lower, 22% vs. 44% (p<0.001). Significantly more patients in decision-aid vs. pamphlet group rated information to be excellent for understanding lupus nephritis (49% vs. 33%), risk factors (43% vs. 27%), medication options (50% vs. 33%; p≤0.003 for all); and the ease of use of materials higher (51% vs. 38%; p=0.006). Conclusion: An individualized decision-aid was effective in reducing decisional conflict for immunosuppressive medications in diverse women with lupus nephritis. Disclosure of Interests: jasvinder singh Shareholder of: Amarin pharmaceuticals and Viking therapeutics, Consultant for: Crealta/Horizon, Fidia, UBM LLC, Medscape, WebMD, the National Institutes of Health and the American College of Rheumatology, Liana Fraenkel: None declared, Candace Green: None declared, Graciela S Alarcon: None declared, Jennifer Barton: None declared, Kenneth Saag Grant/research support from: Amgen, Ironwood/AstraZeneca, Horizon, SOBI, Takeda, Consultant for: Abbvie, Amgen, Ironwood/AstraZeneca, Bayer, Gilead, Horizon, Kowa, Radius, Roche/Genentech, SOBI, Takeda, Teijin, Leslie Hanrahan: None declared, Sandra Raymond: None declared, Robert Kimberly: None declared, Amye Leong: None declared, Elyse Reyes: None declared, Richard Street: None declared, Maria Suarez-Almazor : None declared, Guy Eakin: None declared, Laura Marrow: None declared, Charity Morgan: None declared, Brennda Caro: None declared, Jeffrey Sloan: None declared, Bochra Jandali: None declared, Salvador Garcia: None declared, Jennifer Grossman: None declared, Kevin Winthrop Consultant for: Gilead, Galapagos, Eli Lilly and Company, Abbvie, Pfizer, GSK, Laura Trupin: None declared, Maria Dall'Era Grant/research support from: University has received funds to serve as a site on this clinical study, Consultant for: On Data Monitoring Committee for Janssen, Biogen, and Genentech; on Steering Committee for EMD Serono., Alexa Meara: None declared, Tara Rizvi: None declared, Winn Chatham: None declared, Jinoos Yazdany Grant/research support from: Pfizer, Consultant for: AstraZeneca